Human Monoclonal Antibodies Methods and Protocols - Steinitz, Michael; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2014)
The introduction of monoclonal antibodies revolutionized immunology. The development of human monoclonal antibodies was inspired primarily by the enormous clinical benefits promised by these reagents which can be used as anti-inflammatory reagents, anti-tumor reagents and reagents for passive immunization in a variety of pathologies. Human Monoclonal Antibodies: Methods and Protocols presents technical protocols of cellular and molecular methods for the production, purification and application of human monoclonal antibodies, as well as review articles on related topics of human monoclonal and polyclonal antibodies. Written in the successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, Human Monoclonal Antibodies: Methods and Protocols seeks to serve both professionals and novices with its well-honed methodologies which will prove invaluable in a clinical setting.
Human Monoclonal Antibodies - The Residual Challenge of Antibody Immunogenicity -- Technical and Ethical Limitations in Making Human Monoclonal Antibodies -- Therapeutic Human Monoclonal Antibodies in Inflammatory Diseases -- Therapeutic Human Monoclonal Antibodies Against Cancer -- Polyclonal and Monoclonal Antibodies in the Clinic -- Production of Human Monoclonal Antibodies by the Epstein- Barr Virus Method -- Humanization and Simultaneous Optimization of Monoclonal Antibody -- Chimeric Antibodies -- Recombinant Genetic Libraries and Human Monoclonal Antibodies -- Production of Stabilized scFv Antibody Fragments in the E. coli Bacterial Cytoplasm -- Construction and Production of an IgG-Like Tetravalent Bispecific Antibody, IgG-Single Chain Fv Fusion -- Construction of Human Antibody Gene Libraries and Selection of Antibodies by Phage Display -- Antigen –Specific Human Monoclonal Antibodies from Transgenic Mice -- Phage Display Technology for Human Monoclonal Antibodies -- Antigen-Specific in vitro Immunization: A Source for Human Monoclonal Antibodies -- Methods for Radiolabelling of Monoclonal Antibodies -- Purification of Human Monoclonal Antibodies and Their Fragments -- Idiotype-Specific IVIG for Therapy of Autoimmune Diseases.
Keywords: Immunology; Antibodies; Immunology; Antibodies